Objects of liberty : British women writers and revolutionary souvenirs - Buck, Pamela, 1975- (Early modern feminisms., 2024)
"Objects of Liberty explores the prevalence of souvenirs in British women's writing during the French Revolution and Napoleonic era. It argues that women writers employed the material and memorial object of the souvenir to circulate revolutionary ideas and engage in the masculine realm of political debate. While souvenir collecting was a standard practice of privileged men on the eighteenth-century Grand Tour, women began to partake in this endeavor as political events in France heightened interest in travel to the Continent. Looking at travel accounts by Helen Maria Williams, Mary Wollstonecraft, Catherine and Martha Wilmot, Charlotte Eaton, and Mary Shelley, this study reveals how they used souvenirs to affect political thought in Britain and contribute to conversations about individual and national identity. At a time when gendered beliefs precluded women from full citizenship, they used souvenirs to redefine themselves as legitimate political actors. Objects of Liberty is a story about the ways that women established political power and agency through material culture"--